Novel variants provide differential stabilisation of human equilibrative nucleoside transporter 1 states - Boakes, Jessica C.; Harborne, Steven. P. D.; Ngo, Jessie T. S.; Pliotas, Christos; Goldman, Adrian (Frontiers in Molecular Biosciences, 2022)
Human equilibrative nucleoside transporters (ENTs) represent a major pharmaceutical target for cardiac, cancer and viral therapies. Understanding the molecular basis for transport is crucial for the development of improved therapeutics through structure-based drug design. ENTs have been proposed to utilise an alternating access mechanism of action, similar to that of the major facilitator superfamily. However, ENTs lack functionally-essential features of that superfamily, suggesting that they may use a different transport mechanism. Understanding the molecular basis of their transport requires insight into diverse conformational states. Differences between intermediate states may be discrete and mediated by subtle gating interactions, such as salt bridges. We identified four variants of human ENT isoform 1 (hENT1) at the large intracellular loop (ICL6) and transmembrane helix 7 (TM7) that stabilise the apo-state (∆Tm 0.7 - 1.5 °C). Furthermore, we showed that variants K263A (ICL6) and I282V (TM7) specifically stabilise the inhibitor-bound state of hENT1 (∆∆Tm 5.0 ± 1.7 °C and 3.0 ± 1.8 °C), supporting the role of ICL6 in hENT1 gating. Finally, we showed that, in comparison with wild type, variant T336A is destabilised by nitrobenzylthioinosine (∆∆Tm -4.7 ± 1.1 °C) and binds it seven times worse. This residue may help determine inhibitor and substrate sensitivity. Residue K263 is not present in the solved structures, highlighting the need for further structural data that include the loop regions.